EFFECT OF CALCUSOL TO REDUCE THE CALCIUM CRYSTAL RETENTION IN KIDNEY EPITHELIAL CELLS MODEL OF NEPHROLITHIASIS - Ahmad Soni; Moch. Sasmito Djati; Sri Widyarti (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2013)
Kidney stones is a disease that characterized by a disturbance in the bladder. The main constituent of kidney stones namely Calcium Oxalate Monohydrate (COM) crystals. The presence of a COM crystal adhesion to renal tubular cells, will initiate the internalization which will further lead to the formation of crystals retention in the kidney. In Indonesia, there are many herbal products are considered able to cope the complaints due to the kidney stone disease. One of the herbal product is Calcusol „¢, which is the main constituent of those herbal product was the leaf extract of tempuyung. This study observed the effectiveness of Calcusol „¢ in reducing crystals retention that was formed in kidney epithelial cells model of nephrolithiasis. The result showed that Calcusol „¢ is able to reduce the average number of calcium crystals retention in the renal epithelial cells. It indicate that Calcusol „¢ has the ability to reduce crystals retention that already formed in renal epithelial cells. Furthermore, the results of this study are expected to be one of the considerations for further research on the potential of overcoming Calcusol „¢ in kidney stone disease